2007
DOI: 10.1080/00015458.2007.11680058
|View full text |Cite
|
Sign up to set email alerts
|

Does Preoperative Magnetic Resonance Imaging Modify Breast Cancer Surgery ?

Abstract: Breast MRI could be recommended as a pre-surgical diagnostic procedure in patients allocated to breast conservation surgery. Nevertheless, further studies are needed to determine if preoperative breast MRI leads to a decrease in tumor recurrence and in overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…This study confirms our original hypothesis that preoperative bilateral breast MRI in young women with breast cancer alters surgical management in a significant proportion of patients. This finding is in agreement with several other retrospective and prospective studies evaluating the use of preoperative breast MRI in patients with newly diagnosed breast cancer; [13][14][15][16][17][18][19] however, this is one of the first studies to specifically evaluate a younger patient population.…”
Section: Discussionsupporting
confidence: 92%
“…This study confirms our original hypothesis that preoperative bilateral breast MRI in young women with breast cancer alters surgical management in a significant proportion of patients. This finding is in agreement with several other retrospective and prospective studies evaluating the use of preoperative breast MRI in patients with newly diagnosed breast cancer; [13][14][15][16][17][18][19] however, this is one of the first studies to specifically evaluate a younger patient population.…”
Section: Discussionsupporting
confidence: 92%
“…A spectrum of positive biopsy rates have previously been described for suspicious contralateral breast MRI findings in this patient population. Ours is within the range of 18.8–61.5% for positive biopsy rates that have been reported in the largest prior studies [6, 8, 12, 1417, 20, 5362]. Although we found that sampling by excisional biopsy had a higher positive biopsy rate than that by needle biopsy (42.9% vs 20.5%), the majority of surgical biopsy results, including excisional biopsy, were benign.…”
Section: Discussionsupporting
confidence: 77%
“…There is little doubt that the use of MR data to influence surgical planning has important implications in the surgical management of patients [5,6]. We believe that better image-to-physical data alignment strategies can be used more directly for better surgical management.…”
Section: Introductionmentioning
confidence: 99%